2018
DOI: 10.1177/1535370218803349
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of secretory diarrhea by the lysophosphatidic acid analog Rx100

Abstract: Diarrheal disease is a severe global health problem. It is estimated that secretory diarrhea causes 2.5 million deaths annually among children under the age of five in the developing world. A critical barrier in treating diarrheal disease is lack of easy-to-use effective treatments. While antibiotics may shorten the length and severity of diarrhea, oral rehydration remains the primary approach in managing secretory diarrhea. Existing treatments mostly depend on reconstituting medicines with water that is often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…We have determined that 80% of OTP administered orally is bioavailable, and for this reason we delivered OTP via oral gavage to mice infected with C. rodentium. In this infection model, OTP significantly reduced fecal Cl  secretion and weight loss of mice (54). Because patients with SED also vomit, they often cannot keep down the massive amounts of liquid used as ORT.…”
Section: What Are Other Medical Indications For Therapeutic Use Of Lpmentioning
confidence: 87%
See 1 more Smart Citation
“…We have determined that 80% of OTP administered orally is bioavailable, and for this reason we delivered OTP via oral gavage to mice infected with C. rodentium. In this infection model, OTP significantly reduced fecal Cl  secretion and weight loss of mice (54). Because patients with SED also vomit, they often cannot keep down the massive amounts of liquid used as ORT.…”
Section: What Are Other Medical Indications For Therapeutic Use Of Lpmentioning
confidence: 87%
“…Using open-and closed-intestinal-loop SED models, we have shown that LPA and OTP effectively reduce cholera toxin-induced Cl  secretion into the intestinal lumen (Fig. 4A, B) (23,54). Disruption of the macromolecular complex between LPA 2 and CFTR abrogates the effect of LPA on Cl  secretion (23).…”
Section: What Are Other Medical Indications For Therapeutic Use Of Lpmentioning
confidence: 96%
“…A significant body of evidence indicates that LPA plays a crucial role in the growth and differentiation of intestine as well as the protection of intestinal mucosa from a variety of noxious conditions. 34,36,37,39,40 The endogenous LPA and synthetic analogs such as RP-1 protect the gut from the genotoxic stress-triggered sequelae of pathophysiological events that underlie the acute gastrointestinal radiation syndrome. 29 However, the role of LPA in the protection of the colonic mucosal barrier function is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is less than ideal because in cases where an infection is a cause, it may increase the incidence of bacterial multiplication and the potential for sepsis. [28] Vaccination is also recommended by WHO as a complementary strategy, which involves key measures of water and sanitation interventions, health and hygiene education, strengthening of disease surveillance and oral cholera vaccine (OCV) campaigns in high-risk areas. [29] Oral cholera vaccine is recommended as it provides a short-term solution to bring about an immediate effect to a potential cholera outbreak while other longer-term interventions are put into place.…”
Section: Introductionmentioning
confidence: 99%